Quantitative Proteomics Reveals Changes in Transporter Protein Abundance in Liver, Kidney and Brain of Mice by Pregnancy - Liao, Michael Z.; Gao, Chunying; Bhatt, Deepak K.; Prasad, Bhagwat; Mao, Qingcheng (Drug Metabolism Letters, 2018)
Background: Few studies have systematically investigated pregnancy-induced changes in protein abundance of drug transporters in organs important for drug/xenobiotic disposition. Objective: The goal of this study was to compare protein abundance of important drug/xenobiotic transporters including Abcb1a, Abcg2, Abcc2, and Slco1b2 in the liver, kidney and brain of pregnant mice on gestation day 15 to that of non-pregnant mice. Methods: The mass spectrometry-based proteomics was used to quantify changes in protein abundance of transporters in tissues from pregnant and non-pregnant mice. Results: The protein levels of hepatic Abcc2, Abcc3, and Slco1a4 per μg of total membrane proteins were significantly decreased by pregnancy by 24%, 72%, and 70%, respectively. The protein levels of Abcg2, Abcc2, and Slco2b1 per μg of total membrane proteins in the kidney were significantly decreased by pregnancy by 43%, 50%, and 46%, respectively. After scaling to the whole liver with consideration of increase in liver weight in pregnant mice, the protein abundance of Abcb1a, Abcg2, Abcc2, Abcb11, Abcc4, Slco1a1, and Slco1b2 in the liver was 50-100% higher in pregnant mice, while those of Abcc3 and Slco1a4 were 40% lower. After scaling to the whole kidney, none of the transporters examined were significantly changed by pregnancy. Only Abcg2 and Abcb1a were quantifiable in the brain and their abundance in the brain was not influenced by pregnancy. Conclusion: Protein abundance of drug transporters can be significantly changed particularly in the liver by pregnancy. These results will be helpful to understand pregnancy-induced changes in drug/xenobiotic disposition in the mouse model.
Keywords: Pregnancy